Imposition of Double Charges on Hydroelectric Power Plants - Titah Shanty Saraswati; R. Ismala Dewi (Sociological Jurisprudence Journal, 2024)
In meeting electricity needs, there is currently a shift in the use of fossil energy to water energy because fossil energy is no longer available. The use of water as a new renewable energy, as stated in the Electricity Supply Business Plan (RUPTL), which prioritizes Hydroelectric Power Plants (PLTA), is considered to require lower investment and stable electricity production compared to Solar Power Plants (PLTS) or Wind Power Plants (PLTB). Providing this water requires conservation costs and other water management costs. So the main topic studied in this research is the problems and impacts of the imposition of water fees including Natural Resource Management Services Fees (BJPSDA) and Surface Water Tax (PAP) on water resource conservation. The research used is explanatory doctrinal research using document studies. The results of the research are that apart from the BJPSDA, there is a PAP which has not been subject to earmarking. Both are regulated in different regulations but are imposed on the same object, namely water. Based on the analysis, it is necessary to evaluate how the implementation of the fee has been able to fulfill the community's rights to water and can maintain the sustainability of water availability through water resource conservation. Therefore, it is necessary to reconsider the imposition of double levies on surface water beneficiaries by changing the BJPSDA manager to a party who has a greater interest in water conservation results and applying the PAP earmarking concept.